A rule of thumb for the economic capital of a large credit portfolio - Rafael Weißbach (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2004)
We derive approximate formulae for the credit value-at-risk and the economic capital of a large credit portfolio. The representation allows to change the risk horizon quickly and avoids simulation or numerical procedures. The Poisson mixture model is equivalent to CreditRisk and uses the same parameters.
Keywords: 519; Kreditrisiko; Value at Risk; Portfolio-Management; Eigenkapital; Bilanzstrukturmanagement; Theorie